RNase H activity associated with reverse transcriptase from feline immunodeficiency virus. - Cronn, R C (1992)
Reverse transcription of retroviral genomes requires the action of an RNase H for template switching and primer generation. In this report, we compare enzymatic properties of the RNase H associated with the reverse transcriptase (RT) from feline immunodeficiency virus (FIV) and that from human immunodeficiency virus (HIV). Both enzymes displayed substrate preference for poly[3H](rG) . poly(dC) hybird over poly[3H](rA) . poly(dT) and cation preference for Mg2+ over Mn2+. Activity of the FIV RNase H upon poly(rG) . poly(dC) produced hydrolysis products from 1 to 6 nucleotides in length, similar to that reported for HIV. Dextran sulfates were effective inhibitors of both the FIV and HIV RNase H and RT activities. Nearly identical inhibition constants (0.12 nM) were obtained for all enzyme activities with dextran sulfate 500,000, while different inhibition constants were observed with dextran sulfate 8,000. Our results suggest that FIV and HIV RTs contain a conserved region that is sensitive to the larger dextran sulfate and that dextran sulfate 8,000 may interact at a different site or by a different mechanism.